1988
DOI: 10.1115/1.3173633
|View full text |Cite
|
Sign up to set email alerts
|

On Three-Dimensional Nonlinear Subharmonic Resonant Surface Waves in a Fluid: Part I—Theory

Abstract: Three-dimensional surface waves in a rectangular container subjected to vertical excitation are studied. The analysis includes the effects of surface tension, energy dissipation, and critical depth. Both steady state and transient phenomena are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 0 publications
4
24
0
Order By: Relevance
“…At the critical depth the response changes from a ''hard-spring'' to a ''soft-spring''. Gu et al [20], Faltinsen [11], Waterhouse [41] found h c =k ¼ 0:583 m or in general h c ¼ 0:337 Â b for the first mode, respectively. Since h s is 0.6 m, this particular study is a near critical depth case.…”
Section: Horizontally Excited Tanksmentioning
confidence: 97%
See 1 more Smart Citation
“…At the critical depth the response changes from a ''hard-spring'' to a ''soft-spring''. Gu et al [20], Faltinsen [11], Waterhouse [41] found h c =k ¼ 0:583 m or in general h c ¼ 0:337 Â b for the first mode, respectively. Since h s is 0.6 m, this particular study is a near critical depth case.…”
Section: Horizontally Excited Tanksmentioning
confidence: 97%
“…It has been established that there is a critical liquid depth that delineates two non-linear regimes of the liquid free surface referred to as soft and hard spring characteristics. Gu and Sethna [19], Gu et al [20], Virnig et al [40] have examined the role of the liquid critical depth in rectangular tanks subjected to vertical sinusoidal excitation. Another important feature is that there is an excitation frequency range over which the free surface exhibits chaotic motion [23].…”
Section: Introductionmentioning
confidence: 98%
“…It has been established that there is a critical liquid depth that delineates two nonlinear regimes of the liquid free surface referred to as soft and hard spring characteristics. Gu and Sethna (1987), Gu et al (1988) and Virnig et al (1988) have examined the role of the liquid critical depth in rectangular tanks subjected to vertical sinusoidal excitation. Another important feature is that there is an excitation frequency range over which the free surface exhibits chaotic motion (Ibrahim et al, 2001).…”
Section: Article In Pressmentioning
confidence: 99%
“…Further, the wave steepness, defined as S ¼ k nẑ ¼ 1:2; 0:64 (where k n ¼ np=b is the wavenumber), respectively, versus the wave steepness of 0.0004 of the linear case. Also, this particular tank aspect ratio (b=h ¼ 2) has a water depth above the critical water depth, defined asĥ c =l w ¼ 0:162 (Gu et al, 1988) wherê l w ¼ 2b=n denotes the wavelength. The b=h ¼ 2 is a deep water case as k 1ĥ 4p=2: Note in an uncoupled system the liquid is known to exhibit softening spring behavior whereas the coupled system shows increasing amplitudes with respect to linearly predicted frequencies (as discussed later, e.g., Fig.…”
Section: Case Studiesmentioning
confidence: 99%